Youth Epidemiology and Resilience (YEAR) in a student population: prevalence and predictors of mental health symptoms - Wong, John Chee Meng; Lei, Natalie Cheok Ling; Kom, Dennis Mun Yen; Fee, Victoria Hui Fen; Yap, Natalie Huijing; Teoh, Jie Yu; Shen, Liang; Yap, Qai Ven; Wan, Michelle Jing Si; Du, Ruochen; Kroneman, Leoniek; Fung, Daniel Shuen Sheng; et al. (Frontiers in Psychiatry, 2024)
Background Adolescence is a pivotal developmental phase, marked by a high prevalence of mental health issues. The Singapore Youth Epidemiology and Resilience (YEAR) study aims to assess the prevalence of mental health symptoms, sociodemographic risk factors, and the protective role of resilience in a multi-ethnic, Asian school-going adolescent population. Methods School-based adolescents aged 10-18 and their parents were invited from a stratified sample of national schools, designed to be demographically representative of the mainstream school-going population. In the screening phase, adolescents completed a battery of questionnaires including the Youth Self-Report (YSR), Child Behaviour Checklist (CBCL), and the Singapore Youth Resilience Scale (SYRESS). Thereafter, diagnostic interviews were conducted on high-risk and control participants. Data analysis was conducted to establish prevalence rates of mental health symptoms, and to examine the associations between mental health symptoms, sociodemographic factors, and resilience. Results The final study sample consisted of 3336 adolescents and 2475 parents. Based on adolescents' response on the YSR, 37.3%, 13.1% and 27.7% of the YEAR Study population scored in the clinical range for internalizing, externalizing and total problems respectively. Based on parents' reporting on their children on the CBCL, 15.9%, 4.0% and 11.2% scored in the clinical range for internalizing, externalizing and total problems respectively. Sociodemographic risk factors for specific mental health symptoms were identified, including belonging to the age category of 15-16 (OR, 1.8-2.2) and those living in either a 4-, 5-room or executive flat (OR, 0.6-0.7), or in condominiums and other apartments (OR, 0.4-0.6). Total resilience scores were moderately correlated with total [rs(3334) = -.49, p <.01] and internalizing [rs(3334) = -.50, p <.01] problem scores on the YSR. Conclusion This study illustrates the state of mental health of school-going adolescents aged 10-18. The greater prevalence of internalizing symptoms indicates the need for stronger attention for identifying internalizing problems and targeted interventions for those at risk of such symptoms. The association between mental health symptoms and resilience factors highlights the protective potential of resilience building for adolescents.